2020
DOI: 10.1101/2020.09.13.20188334
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Self-collected Saline Gargle Samples as an Alternative to Healthcare Worker Collected Nasopharyngeal Swabs for COVID-19 Diagnosis in Outpatients

Abstract: Background: We assessed the performance, stability, and user acceptability of swab-independent self-collected saliva and saline mouth rinse/gargle sample types for the molecular detection of SARS-CoV-2 in adults and school-aged children. Methods: Outpatients who had recently been diagnosed with COVID-19 or were presenting with suspected COVID-19 were asked to have a nasopharyngeal swab collected and provide at least one self-collected sample type. A portion of participants were also asked about sample acceptab… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…We considered clearing the throat important to sample material from the posterior oropharynx, where SARS-CoV-2 sampling by oropharyngeal swabs is known to be efficient [ 34 , 35 ]. While gargling with saline or buffer solutions has been suggested as a possibility to sample saliva from the deep throat [ 36 , 37 ], we rated this procedure as less operable as the gargling solution would need to be optimized for taste to be accepted by individuals, could not include preservatives and gargling itself may potentially generate aerosols. In addition, gargling is not practicable for many younger children, for whom we particularly sought to create more possibilities for SARS-CoV-2 testing, as NPS collection is often not practical in children.…”
Section: Discussionmentioning
confidence: 99%
“…We considered clearing the throat important to sample material from the posterior oropharynx, where SARS-CoV-2 sampling by oropharyngeal swabs is known to be efficient [ 34 , 35 ]. While gargling with saline or buffer solutions has been suggested as a possibility to sample saliva from the deep throat [ 36 , 37 ], we rated this procedure as less operable as the gargling solution would need to be optimized for taste to be accepted by individuals, could not include preservatives and gargling itself may potentially generate aerosols. In addition, gargling is not practicable for many younger children, for whom we particularly sought to create more possibilities for SARS-CoV-2 testing, as NPS collection is often not practical in children.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that self-collected saline mouth rinse/gargle samples had similar performance as NPFS for detection of SARS-CoV-2 in adults and children presenting with outpatient illness (Goldfarb et al, 2020). In the present work, we seek to evaluate this sample type with a simplified process for detecting SARS-CoV-2, without RNA extraction (extraction-free PCR; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 One aspect of this debate concerns the occurrence of SARS-CoV-2 infection in children compared to adults. In our study, we detected SARS-CoV-2 infection in 1.42% (95% CI 1.06-1.90%) of study participants at the second round of examinations (10)(11)(12)(13)(14)(15)(16). This prevalence was somewhat less than the screen-detected prevalence of 2.12% in adults, which was observed by a different nationwide population-based study 21 conducted at a similar time frame (12-14 November, 48 out of 2263 tests positive based on nasopharyngeal swabs).…”
Section: Discussionmentioning
confidence: 50%
“…Gargling has been demonstrated to produce comparable sample quality like throat swab samples for other respiratory viruses 11 and has also been applied successfully for the detection of SARS-CoV-2. [12][13][14][15] At the laboratories, sample inactivation, RNA extraction, and RT-qPCR detection of SARS-CoV-2 was performed according to previously established protocols (for details, see Supplementary Material). Gargling samples were analysed in pools with a maximal pool size of 10.…”
Section: Sars-cov-2 Detection By Rt-pcrmentioning
confidence: 99%